Fermentation of Light and Dark Bean Coffee Brews with SCOBY and Lactic Acid Bacteria - Rusen Metin Yildirim (Fermentation)
This study investigated the effects of fermentation with a SCOBY (symbiotic culture of bacteria and yeast) and lactic acid bacteria (LAB) on the physicochemical and sensory properties of coffee brews prepared from light-roasted (LR) and dark-roasted (DR) coffee beans, with and without the addition of spent coffee grounds (SC). Total phenolic content (TPC), total flavonoid content (TFC), antioxidant activities (DPPH and FRAP), caffeine, and individual phenolic acids were analyzed. Fermentation significantly increased TPC and the concentrations of chlorogenic acids (CGAs), particularly in LR samples, with 5-caffeoylquinic acid (5-CQA) as the most abundant phenolic acid. The addition of spent coffee grounds further enhanced TPC and CGA levels, with total CGA concentrations increasing from 1412.32 to 2458.57 mg/L in LR samples and from 519.77 to 586.37 mg/L in DR samples. Fermentation also led to the isomerization of 5-CQA into 3-CQA and 4-CQA, as well as the release of caffeic acid in LAB-fermented samples. Acetic acid production was exclusive to SCOBY-fermented samples, with higher levels in LR samples (6658 mg/L) compared to DR samples (4331 mg/L). In contrast, lactic acid production was observed only in LAB-fermented samples, reaching 6559 mg/L in LR samples with spent coffee grounds. Antioxidant activity varied depending on the assay, with FRAP values decreasing in fermented samples, while DPPH values remained largely unchanged. Sensory evaluation identified the dark-roasted SCOBY-fermented sample with spent coffee grounds (SK) as the most preferred, characterized by balanced flavor and high overall acceptability. These findings highlight the influence of roasting degree, fermentation type, and substrate composition on the bioactive and sensory properties of fermented coffee, providing insights for the development of novel coffee-based fermented beverages with enhanced functional and sensory profiles.